2003
DOI: 10.1111/j.1521-0391.2003.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Diagnosis: Alcoholism and Co‐Morbid Psychiatric Disorders

Abstract: Although alcohol use disorders are commonly associated with co‐morbid drug use and psychiatric disorders, such co‐morbidity is frequently underdiagnosed and inadequately treated. This paper reviews the epidemiological, diagnostic, and treatment literature on the co‐morbidity of alcoholism, with a focus on the most common co‐morbid disorders: drug abuse, mood disorders, anxiety disorders, and antisocial personality disorder. The paper goes on to describe a number of promising approaches to the treatment of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 74 publications
2
39
2
1
Order By: Relevance
“…Instead, A+PD showed more extensive abuse of medicine/drugs, especially A+PDB. This has also been found in other studies, where these patients had a greater prevalence of drug and alcohol abuse [7,18,19] . However, it should be emphasized that very few of our patients had a drug abuse problem, and it was always abuse of either benzodiazepines or cannabis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Instead, A+PD showed more extensive abuse of medicine/drugs, especially A+PDB. This has also been found in other studies, where these patients had a greater prevalence of drug and alcohol abuse [7,18,19] . However, it should be emphasized that very few of our patients had a drug abuse problem, and it was always abuse of either benzodiazepines or cannabis.…”
Section: Discussionsupporting
confidence: 85%
“…The young age of A+PDB may have been due to the early onset of the alcohol abuse, so that at the time of the interview they had been abusing alcohol for longer than the rest of the patients. In other studies, dissocial alcoholics were found to have an earlier onset of alcohol use [19,22] . Young age, being male and having serious problems combined with alcohol abuse also correlates with Cloninger's type 2 and Babor's type B alcoholics, and a new study has reported that type B includes significantly more PDB [22] .…”
Section: Discussionmentioning
confidence: 72%
“…However, Cluster B PDs appear to be particularly prevalent among alcoholics, 2,3,[5][6][7]10,11,13 with both ASPD and BPD overrepresented in this population. 1,6,8,11,[21][22][23][24] In turn, alcohol use disorders are highly prevalent among people with Cluster B PDs. In the NESARC, alcohol use disorders were more frequently encountered among the 2 Cluster B PDs studied (in 28.7 % of people with ASPD and in 29.1% of those with histrionic PD) than those with other types of PDs.…”
mentioning
confidence: 99%
“…alcohol and other psychoactive substances are also associated with a higher incidence of depression and a higher risk of suicide, although the association between depression and alcohol addiction is not as strong as in bipolar affective disorder [30][31][32]. in Poland, 10.9% of subjects abuse alcohol, including 18.6% of men.…”
Section: Medical Historymentioning
confidence: 99%